Urban infrastructure development-human security nexus: Flows, spaces, and livelihoods framework for comparative research in Africa's post-colonies - Mbiba, Beacon (Frontiers in Sustainable Cities, 2022)
Abstract This desktop study paper suggests a ‘flows and livelihoods’ framework for comparative studies on ‘displaceability’ in the context of infrastructure and investment/projects in diverse post-colonial settings. It uses the ongoing upgrading of Mbudzi (Goats) interchange, in Harare, to discuss the utility of this framework in addressing diverse sustainability and human security questions irrespective of scale, scope and settings of the project. Thus, the paper contributes to integrated ways of understanding dynamics and sustainability of infrastructure investments. In the process, it also responds to Rydin’s (2021) call on the need for exemplars on how theory can be integrated into planning research. Ultimately, what it offers is a heuristic device for cross-sectional and time-series studies.